2016
DOI: 10.1364/oe.24.002619
|View full text |Cite
|
Sign up to set email alerts
|

Secure polarization-independent subcarrier quantum key distribution in optical fiber channel using BB84 protocol with a strong reference

Abstract: A quantum key distribution system based on the subcarrier wave modulation method has been demonstrated which employs the BB84 protocol with a strong reference to generate secure bits at a rate of 16.5 kbit/s with an error of 0.5% over an optical channel of 10 dB loss, and 18 bits/s with an error of 0.75% over 25 dB of channel loss. To the best of our knowledge, these results represent the highest channel loss reported for secure quantum key distribution using the subcarrier wave approach. A passive unidirectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 33 publications
0
75
0
Order By: Relevance
“…Although this system used a DPS-QKD demonstrator as the underlying optical system, there is no reason to believe that the performance of a phase-encoded BB84 type system would be significantly different in terms of time to sign bits at these levels of channel loss. By demonstrating that QDS protocols can be applied to an alternative QKD protocol, other than BB84, this work has shown that there is scope for use of QDS with further alternative QKD systems such as coherent-one-way 38 or sub-carrier wave 39 . With revised protocols for signatures offering the possibility of even greater enhancements in signature generation rate 40 , the prospect of commercial systems capable of offering both QKD and QDS, depending on the end application required, is potentially close and recent developments in chip scale QKD systems 41 also offer the prospect of compact chip scale QDS systems.…”
Section: Resultsmentioning
confidence: 92%
“…Although this system used a DPS-QKD demonstrator as the underlying optical system, there is no reason to believe that the performance of a phase-encoded BB84 type system would be significantly different in terms of time to sign bits at these levels of channel loss. By demonstrating that QDS protocols can be applied to an alternative QKD protocol, other than BB84, this work has shown that there is scope for use of QDS with further alternative QKD systems such as coherent-one-way 38 or sub-carrier wave 39 . With revised protocols for signatures offering the possibility of even greater enhancements in signature generation rate 40 , the prospect of commercial systems capable of offering both QKD and QDS, depending on the end application required, is potentially close and recent developments in chip scale QKD systems 41 also offer the prospect of compact chip scale QDS systems.…”
Section: Resultsmentioning
confidence: 92%
“…The parameters of the signal field are determined by the requirements of the protocol of quantum communication. Encoding in a QCSF system with homodyne detection can be done via quadrature modulation of the radio frequency control signal, and is also determined by a protocol [9].…”
Section: Using a Heterodyne Detection Scheme In A Subcarrier Wave Quamentioning
confidence: 99%
“…Thereby, the problem of system synchronization is reduced to fine tuning of the transmitter and receiver oscillators. Detailed descriptions of phase modulating in a SCWQC system are provided in [8,9].…”
Section: Process Modelingmentioning
confidence: 99%
“…The Ω value is typically several gigahertz for SCWQC systems [3,8]; we used a value of 4 GHz in our calculations. Therefore, the maximum tolerable synchronization signal time delay is 1.7 ps.…”
Section: Process Modelingmentioning
confidence: 99%